Marine Academy May Lose Its Ship - Abramson, Mike (Oakland Tribune)
Pride of the California Maritime Academy, and its most important training aid, is the Golden Bear, but the ship's future in the school's program is in doubt pending a report by the Senate Subcommittee on Merchant Marine and Fisheries, the high point of the Academy's year is the annual training cruise which has carried California midshipmen in the past from Gibraltar to Tahiti.